2012
DOI: 10.1111/j.1365-2184.2012.00808.x
|View full text |Cite
|
Sign up to set email alerts
|

Basic fibroblast growth factor modulates cell cycle of human umbilical cord‐derived mesenchymal stem cells

Abstract: Our study showed that bFGF supplementation of UC-MSC culture enhanced the cells' growth kinetics without compromising their nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 35 publications
(37 reference statements)
5
29
0
Order By: Relevance
“…Thus, we compared growth, phenotype, differentiation potential, metabolism, and longevity of UC-MSC cultured in xeno-free media to control cells propagated in standard serum-based medium (with 10 % FBS; M6) and serum-reduced medium (5 % FBS) supplemented with bFGF (5 ng/mL; M7), since bFGF has been shown to enhance proliferation of UC-MSCs [27]. A scheme of experimental procedures is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we compared growth, phenotype, differentiation potential, metabolism, and longevity of UC-MSC cultured in xeno-free media to control cells propagated in standard serum-based medium (with 10 % FBS; M6) and serum-reduced medium (5 % FBS) supplemented with bFGF (5 ng/mL; M7), since bFGF has been shown to enhance proliferation of UC-MSCs [27]. A scheme of experimental procedures is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are supported by our own data, clearly indicating acceleration of proliferation from the beginning of FGF-2 administration, and improved chondrogenic outcome for FGF-2 augmented groups. It has recently been shown that FGF-2 improves proliferation of umbilical cord-derived MSCs (UC-MSCs), but that their 'nature' remains unaffected, as reflected by immunophenotype and immunomodulatory properties (49), although it was also clearly stated that cytokine profiles were significantly altered by FGF administration. However, those authors noted that their cells met all criteria for MSCs defined by the International Society for Cellular Therapy (ISCT) (19), although these data were not shown (49).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study it was also observed that late EPCs cultured in EGM-2MV exhibit a greater number of apoptotic cells. Ramasamy et al (26) demonstrated that elevated expression of stem cell-associated transcription factors is correlated with a reduction in cell apoptosis. As EGM-2MV is the medium that most strongly supports the differentiation of EPCs towards endothelial cells, it is reasonable that a greater number of apoptotic cells were observed in late EPCs in the EGM-2MV medium.…”
Section: Discussionmentioning
confidence: 99%